A GIS based assessment of urban sprawl in North Khobar. (12th April 2010) - Al-Dosary, Adel S.; Khan, Feroz
Urban sprawl has turn out to be an issue of worldwide interest, mainly because of its alleged negative impacts on the social, economic and environmental aspects of the city. Many studies indicate that it is the pattern, density, and rate of new urban growth that leads to sprawl. The proportion of the total population in a region to the total built-up area of the region is a measure of quantifying sprawl. This paper presents a quantitative method to analyse urban sprawl based on computation of indicators and GIS techniques. It was found out that for the study area the percentage change in the built-up area (1980-2005) was 14 times higher than the percentage change in the population growth, and also with the analysis capabilities in GIS, it determined the patterns and densities of new growth thereby classifying some of those areas as sprawl patterns.